Dėl akcentinės lietuvių kalbos vardažodžių priesagų galios - Pakerys, Antanas (Baltistica, 2008)
On the accentual value of Lithuanian nominal suffixesThis paper presents some remarks on the definition of accentual value of Lithuanian nominal suffixes. All of these suffixes determine the accentuation of derivatives and, therefore, these morphemes can be considered as dominant. It is argued in this paper that the classification of nominal suffixes into strengthening and weakening ones should be based on the effect these suffixes make on the stems of the derivatives rather than on the stems of the base words. One should note that the weakening suffixes can be not only weak, but also strong in some cases. The description of strong suffixes should not be limited to indicating whether they are acute or non-acute. If the vocal phonemes of the suffix belong to two syllables, the place of the stress also has to be taken into account. In a number of cases the accentual properties of suffixes are conditional (i.e. when the derivatives of these suffixes are described, additional rules have to be provided or at least the irregular items have to be listed). On the other hand, one should note that the majority of suffixes are unconditional (the accentuation of their derivatives is not related to certain conditions).
Keywords: lietuvių kalba; vardažodis; priesaga; akcentologija; akcentinė galia; morfemų akcentinės savybės